Water: As a Social Order Decider in Central Himalayas - Sandeep Kumar (Integrated Journal for Research in Arts and Humanities, 2022)
Any direct or indirect change in the physical, thermal, chemical, biological, radioactive properties of any part of the environment, by discharge, emissions or deposits of waste, so as to adversely affect any beneficial use or a condition which Hazardous to public health, safety or to animals, birds, wildlife, aquatic life or plants of all kinds. - Environment Report 1986 The concept of the present paper begins with the concept of water, forest, and land, which has been an important motto and main goal of an important movement (Chipko movement)- What is the blessing of the forest (क्या है जंगल के उपकार) soil water and wind (मिट्टी पानी और बयार) soil water and wind (मिट्टी पानी और बयार) basis for survival. (जिंदा रहने के आधार।) When it comes to the basic three things that have been described as the basis of life - forest, land and water, these three have equal access to every community, class, caste. and do they have access at present? the present research paper focuses on water and its access. Is. Especially its access to the community which comes under the purview of the marginalized society.